Effects of inbreeding on reproductive parameters of Costa Rican Holstein and Jersey cows. - Aguirre-Valverde, Judyana (2013)
The objective ofthis study was to analyze the effect of high inbreeding (F)levels (≥ 6.25%) on reproductive parameters of Holstein andJersey cows born between Jan 1995 and Dec 2010 in specializeddairy herds in Costa Rica. Data on age at first calving(AFC), open days (DO) and services per conception (SPC)from (n=263 804) from the VAMPP national data base, at theVeterinary School of the Universidad Nacional, was used.An F value ≥ 6.25% (high/risk) was used as a cut-off point.The data were processed using descriptive statistics, multiplelinear regression (mixed model), and logistic regression. A17.9% of animals had some inbreeding, with an F average of0.42% (0.49% and 0.55% for Holstein and Jersey). 22.6% ofHolstein and 20.3% of Jersey were inbreed; however, in Jersey,there were cows with higher F. Cows with some inbreedinghave an average F of 2.16% for Holstein and 2.98% forJersey. Furthermore, cows with low F had 18 d less of AFC(p<0.01) compared to those with high F. Regarding the DO,there were +0.53 d for animals with low F (P= 0.71); whilethe cows with low F had +0.08 SPC (P<0.01). There was norisk of DO or SPC in animals with F ≥ 6.25%; which occurredfor AFC (OR = 1.23; 95% CI: 1.10-1.38). Accordingto this study, inbreeding did not affect the DO, but slightlyaffects the SPC and the AFC in Holstein and Jersey cows.